(untitled) - Nathan J Muller (New York, 2000)
The book provides the broad, up-to-date coverage needed by both communications professionals and beginners in this fast-moving, acronym-riddled field. It offers full explanations of important developments and technologies in clear, nontechnical language.
Keywords: data transmission systems - encyclopedias,telecommunication systems - encyclopedias